A Salmonella Typhimurium outbreak linked to Vietnamese bread rolls in South Western Sydney, Australia, 2015 - Chandra, Meena; Lord, Heidi; Fletcher-Lartey, Stephanie; Alexander, Kate; Egana, Nilva; Conaty, Stephen (Western Pacific Surveillance and Response, 2017)
Introduction: In September 2015, the South Western Sydney (SWS) Public Health Unit was notified of a cluster of Salmonella Typhimurium (STm) cases with a common multiple-locus variable-number tandem repeats analysis (MLVA) pattern. An investigation was conducted to identify a source and contain the outbreak.Methods: The cluster was initially identified through routine geographic information system cluster scanning applied to the New South Wales Notifiable Conditions Management System. Additional cases were identified through a complaint to local council about a bakery. The bakery was inspected and 48 environmental and food swabs were collected for analysis.Results: A total of 26 suspected cases were identified, of which 14 were interviewed. STm MLVA type 3–16–9-11–523 was identified in 19 of 26 case stool specimens. Most cases (12/14) consumed bread rolls containing pork or chicken with chicken liver pâté and raw egg mayonnaise filling. Five cases identified a common bakery exposure. Environmental and food samples from the bakery isolated STm with an identical MLVA pattern.Discussion: An STm cluster in SWS was investigated and found to be linked to Vietnamese bread rolls containing pork or chicken with chicken liver pâté and raw egg mayonnaise filling. Confirmation of a distinct MLVA pattern among STm isolates from clinical, food and environmental samples provided evidence to establish an epidemiological link between the cases and the implicated premises and informed public health action to contain the outbreak.